Antioxidant properties and quantitative UPLC-MS/MS analysis of phenolic compounds in dandelion (Taraxacum officinale) root extracts - Kenny, Owen; Smyth, Thomas J.; M. Hewage, Chandralal; P. Brunton, Nigel (Free Radicals and Antioxidants)
Introduction: There is an increasing effort worldwide to investigate the antioxidant efficacy of traditional medicinal plants, which may be used to alleviate oxidative stress synonymous with the pathophysiology of many metabolic disorders as well as prevent oxidative deterioration of food products. In this study the antioxidant potential of dandelion (Taraxacum officinale) root was evaluated. Methods: The radical scavenging and antioxidant activities of solid-liquid extracts from freeze dried dandelion root was measuring in vitro using the modified DPPH and FRAP colorimetric assay. The phenolic content was also evaluated in vitro using the Folin-Ciocaltteu colorimetric assay. Subsequent identification and quantification of phenolic in active extracts was carried out using UPLC-MS/MS. Results: The ethyl acetate crude extract (E3) demonstrated the highest antioxidant activity for both the DPPH (227.728 ± 11.849 mg TE/g) and FRAP (463.066 ± 3.942 mg TE/g) assays. This extract also contained the highest phenolic content (228.723 ± 2.392 mg GAE/g). UPLC-MS/MS was used to identify and quantify phenolic compounds from E3 extract using an internal library of 36 phenolic standards. In total 18 phenolic compounds were quantified with chlorogenic acid, caffeic acid, syringic and vanillic being the most abundant compounds. The flavonoids apigenin-7-O-glycoside, luteolin-7-O-glycoside and naringenin-7-O-glycoside were detected for the first time in dandelion root. Conclusion: The results of this study suggest that dandelion root is a good source of natural antioxidants and could be used in foods with the potential to delay the onset of diseases linked to metabolic derived reactive oxygen species (ROS).
Keywords: Taraxacum officinale; Polyphenols; Radical scavenging; Antioxidant activity; UPLC-MS/MS